2022
DOI: 10.1177/0308518x221130080
|View full text |Cite
|
Sign up to set email alerts
|

Locating state capitalism: Financial centres and the internationalisation of Chinese banks in London

Abstract: This paper examines the internationalisation of Chinese state-owned commercial banks in London's financial centre from the 2010s onwards. These banks have transformed from primarily servicing Chinese state-owned enterprises to making up four of the largest banks globally by balance sheet and undertaking a range of operations including RMB clearing and cross border settlement and yet their future international trajectory remains uncertain. My analysis positions Chinese bank internationalisation within the wider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Some of the socio-spatial relations that have been investigated – and will undoubtedly continue to yield fresh insights into the polymorphous geographies of contemporary state capitalism – include Sperber's (2022) complex relational geographies of social class undergirding state capitalism; political connections between state and business elites ( Wood et al, 2023 ); geopolitics ( Kinossian and Morgan, 2023 ; Ward et al, 2023 ); social relations of production and labor transformations ( Alami and Dixon, 2023 ); relations of empire ( Eagleton-Pierce, 2023 ; Silverwood and Berry, 2023 ; Whiteside, 2023 ); territorial relations at a range of scales ( Su and Lim, 2023 ); networks of production ( McGregor and Coe, 2023 ); corporate ownership ( Babić, 2023 ; Babic et al, 2020 ; Haberly and Wójcik, 2017 ); and finance ( Hall, 2023 ; Petry et al, 2023 ; Sokol, 2023 ). There is also considerable scope for further expanding the socio-spatial relations under consideration in state capitalism research, as some recent contributions have creatively shown (e.g.…”
Section: Centring Relationality In the New State Capitalismmentioning
confidence: 99%
“…Some of the socio-spatial relations that have been investigated – and will undoubtedly continue to yield fresh insights into the polymorphous geographies of contemporary state capitalism – include Sperber's (2022) complex relational geographies of social class undergirding state capitalism; political connections between state and business elites ( Wood et al, 2023 ); geopolitics ( Kinossian and Morgan, 2023 ; Ward et al, 2023 ); social relations of production and labor transformations ( Alami and Dixon, 2023 ); relations of empire ( Eagleton-Pierce, 2023 ; Silverwood and Berry, 2023 ; Whiteside, 2023 ); territorial relations at a range of scales ( Su and Lim, 2023 ); networks of production ( McGregor and Coe, 2023 ); corporate ownership ( Babić, 2023 ; Babic et al, 2020 ; Haberly and Wójcik, 2017 ); and finance ( Hall, 2023 ; Petry et al, 2023 ; Sokol, 2023 ). There is also considerable scope for further expanding the socio-spatial relations under consideration in state capitalism research, as some recent contributions have creatively shown (e.g.…”
Section: Centring Relationality In the New State Capitalismmentioning
confidence: 99%
“…What Meulbroek's contribution offers, ultimately, is a case for engaging with the complexity, contradictions, and (inter)connections among and inside the social-institutional formations that too often are taken to represent "statist" and "neoliberal" models tout court-a call with implications beyond state capitalism studies. Hall (2023), in her contribution focusing on the internationalization of Chinese state-owned banks in London, adopts a similar, spatially sensitive analytical frame. Like Meulbroek's strategic empirical choice to concentrate on the relations between the Chinese state and the World Bank, Hall's analytical strategy is apposite for unsettling binary or exceptionalist readings of state capitalism, while also moving beyond (or below) nation-state framings.…”
Section: State Capitalism As Conjunctural Framementioning
confidence: 99%
“…Hall (2023), in her contribution focusing on the internationalization of Chinese state-owned banks in London, adopts a similar, spatially sensitive analytical frame. Like Meulbroek's strategic empirical choice to concentrate on the relations between the Chinese state and the World Bank, Hall's analytical strategy is apposite for unsettling binary or exceptionalist readings of state capitalism, while also moving beyond (or below) nation-state framings.…”
Section: State Capitalism As Conjunctural Framementioning
confidence: 99%
See 1 more Smart Citation
“…In this theme issue, we can see how both socio-material infrastructures and Mann-like infrastructural power are both at work. Hall's (2022) article examines how International Financial Centres like London shape the governance of financial networks and in so doing, facilitate broader geopolitical changes. The article examines how China's global ambitions in the new normal period have been advanced through the enrolment of London's financial infrastructure to internationalize the Renminbi.…”
Section: Financial Institutionsmentioning
confidence: 99%